2021
DOI: 10.1038/s41598-021-83471-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical treatment outcomes for surgical candidates with lumbar disc herniation: a comprehensive cohort study

Abstract: Physicians often encounter surgical candidates with lumbar disc herniation (LDH) who request non-surgical management even though surgery is recommended. However, second opinions may differ among doctors. Therefore, a prospective comprehensive cohort study (CCS) was designed to assess outcomes of nonsurgical treatment for surgical candidates who were recommended to undergo surgery for LDH but requested a second opinion. The CCS includes both randomized and observational cohorts, comprising a nonsurgery cohort a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Also, it was in the same line with Kim et. al, (2020) (30) who reported that more than one third of the patients undergoing disc surgeries were smokers . Furthermore, it was in the same line with Ali and Hamed (2019) (31) who mentioned that two thirds of the studied group patients undergoing disc surgeries had a herniated lumbar disk from 6 to 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was in the same line with Kim et. al, (2020) (30) who reported that more than one third of the patients undergoing disc surgeries were smokers . Furthermore, it was in the same line with Ali and Hamed (2019) (31) who mentioned that two thirds of the studied group patients undergoing disc surgeries had a herniated lumbar disk from 6 to 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on Epidemiological Information 7 statistical Program. The final acceptable sample size was estimated to be 60 patients.They were divided into two equal groups; 30 patients for each group as following: Group (1): Control group, Consisted of (30) patients who were exposed to routine hospital care. Group (2): Study group, Consisted of (30) patients who were exposed to the protocol of care that was designed and implemented by the researcher.…”
Section: Settingmentioning
confidence: 99%
“…HNP accounts for about two-thirds of spinal pain diagnoses. L4-L5 and L5-S1 are the most frequently affected by herniation [9], [10], [11] and the pain radiates to the lower extremities [12] Its prevalence is approximately 40% in the adult population and disc herniation is the cause [13]. In the United States, HNP is 1 of the 10 most common diseases with a prevalence ranging from 7.6-37% and is found at the age of 45-60 years.…”
Section: Introductionmentioning
confidence: 99%
“…The LDH is common in people aged 25 to 55 spending large percent of times sitting or standing with heavy workload. Current clinical treatment of LDH includes surgical treatment and nonsurgical treatment [ 3 , 4 ]. Although the effect of surgical treatment is good, it faces the risk of nerve injury and adjacent vertebral bodies and recurrence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%